2015
DOI: 10.5625/lar.2015.31.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentoxifylline administration on histomorphological parameters of streptozotocin-induced diabetic rat testes

Abstract: The effect of pentoxifylline (PTX) administration on histomorphological parameters of streptozotocin (STZ)-induced type 1 diabetes mellitus (DM) in male rat testes were evaluated. We randomly divided 40 male rats into the following four groups: group 1: control or normal glycemic (NG) rats; group 2 or NG rats that received only normal saline (NS), (NG+NS); group 3 or diabetic rats which were not treated by PTX (DM+vehicle solution (NS)); and group 4 which comprised diabetic rats treated with 50 mg/kg of PTX (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In other words, we quantitatively determined that PTX exerts its therapeutic effect on seminiferous tubule architecture. Furthermore, present study followed the fate of produced cells of testis, spermatozoa, evaluated sugar and testosterone blood serum levels in diabetic mice, rather than that study (Piryaei et al ., ), confirming the efficacy of PTX for both reliving the dangerous effect of diabetes on male reproductive system and decreasing the high blood glucose of diabetic mice. The study also showed that PTX inhibits cell death in testis of diabetic mice as the same as Piryaei and colleagues have shown (Piryaei et al ., ) and the antioxidant properties of PTX may explain this status as follows.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In other words, we quantitatively determined that PTX exerts its therapeutic effect on seminiferous tubule architecture. Furthermore, present study followed the fate of produced cells of testis, spermatozoa, evaluated sugar and testosterone blood serum levels in diabetic mice, rather than that study (Piryaei et al ., ), confirming the efficacy of PTX for both reliving the dangerous effect of diabetes on male reproductive system and decreasing the high blood glucose of diabetic mice. The study also showed that PTX inhibits cell death in testis of diabetic mice as the same as Piryaei and colleagues have shown (Piryaei et al ., ) and the antioxidant properties of PTX may explain this status as follows.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, Piryaei et al . () showed that PTX improves spermatogenesis of diabetic rats by evaluating Johnson score. To achieve more reliable data, we examined a quantitative method, evaluation of seminiferous diameter, to show the effects of PTX on histopathological changes due to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DM has increased rapidly. The World Health Organization (WHO) has estimated that the number of patients with DM is anticipated to progress to 366 million by 2030 [5, 26, 41]. DM can result in many systemic complications, such as complication in the heart, kidneys, peripheral nerves and reproductive system [5, 9].…”
mentioning
confidence: 99%
“…In line with our findings, Piryaei et al . showed through evaluating Johnsen's score that diabetes impaired spermatogenesis of diabetic rats (Piryaei, Najar, & Bayat, ). Sodium nitrite or insulin treatment resulted in an increased Johnsen's score toward that of controls.…”
Section: Discussionmentioning
confidence: 99%